ASSESSMENT AND SOLUTION OF PROBLEMS OF IMPLEMENTATION OF GOVERNMENT MEDICINE REIMBURSEMENT PROGRAMS IN UKRAINE (World Science, 2020)
The article analyzes the problems of implementation of drug reimbursement programs in Ukraine and in the countries of the world. One of the key problems in the countries of the world is the low index of cooperation between the doctor and the pharmacist, the patient's failure to adhere to the medication regimen and the recommendations of specialists. In Ukraine through questionnaires specialists found that one of the main problems is the unavailability of feedback through the "doctor-pharmacist-patient" and the interaction doctor pharmacist no number of monitoring of medical appointments. The need for close cooperation between doctors, pharmacists, patients and the state in order to justify improving the delivery and receipt of appropriate medical and pharmaceutical care.